Impacto de agrotóxicos usados na lavoura de arroz irrigado em organismos bentônicos - Baumart, Joele Schmitt (2010)
The objective of this project was to investigate the impact of different pesticides used in the ricefield on the density and diversity of benthic organisms. In the experiment, two collects of soil were made to identify and quantify benthic organisms, one in the 28th and other in the 84th days after the entry of water in the ricefield. We used a cylindrical collector of PVC (Curer) with 0.10 m in diameter (0.01 m2) at a depth of 0.10 m. Samples were collected in the irrigated plots that received the following treatments: TO - Imazethapyr + Imazapic (ONLY ®), TB - Bispyribac-sodium (NOMINEE 400SC), TQ - Quinclorac (FACET PM), TF - Fipronil (STANDACK) and TC - control. The number of replicates for each treatment was 12 samples per day. The collected material was stored in plastic bags and taken to the laboratory, where it was washed in sieves of 0.25 mm and re-packed in plastic bottles and then immediately stained (Rose-Bengal), and fixed with absolute ethanol. After fixing, the organisms were separated and identified to the lowest taxonomic level possible, using specialized bibliographies. Throughout the period of ricefield, data on the following parameters of irrigation water were recorded: dissolved oxygen, pH, temperature, alkalinity, hardness, turbidity, conductivity and persistence of pesticides used. To verify differences in the physical-chemical, between treatments, we used a TWO-WAY-ANOVA (treatment and time) and a PCA. An ANOVA one criterion was used to verify differences in taxa between treatments and a MANOVA was used to examine differences in fauna composition between treatments and trophic guilds. There were no differences among abiotic data and the treatment, but differences were found in the time of cultivation. Concerning the persistence of pesticides, the herbicide quinclorac was the most persistent, detected up to the 84th day. The lower persistence of the herbicide ONLY® was detected until the 21st day. In the first sample a total of 1971 animals was collected from all treatments, separated into four phyla: Arthropoda (Insecta, Arachnida and Crustacea), Mollusca (Gastropoda), Anellida (Oligochaeta and Hirudinea) and Nematoda. In the second group of samples, 2295 individuals were identified among all treatments. The same phyla were present, but the diversity of insects was higher than in the previous collection. The MANOVA showed differences between the fauna composition of the treatments evaluated, and between collections, as well as among the fauna composition of the same trophic guild in the different treatments. Based on these results we conclude that the pesticides did not affect the physical and chemical parameters of water, however, these products can cause stress on the benthic community at the beginning of culture for a period of approximately one month after the entry of water in the plots. This effect is reduced over time so that the benthic community tends to restructure after the period of greatest activity of pesticides in water.